Adding vibrations during high intensity cycling increases acute physiological responses - Duc, S.; Urianstad, T.; Rønnestad, B. (Journal of Science and Cycling, 2021)
The purpose of this study was to evaluate the acute physiological effects of adding vibrations to a HIT cycling session characterized by alternating power exercise intensity between lactate threshold (LT) and VO2max during the work intervals. Twelve trained male cyclists performed two 6 x 5 min work intervals training sessionsthat consisted of with between. Each interval included 3 x [40s@WVO2max-1 min@WLT+20%) and was followed by 2.5 min recovery period at low intensity. During one of these two tests and in a random order, vertical synchronous vibrations (40 Hz, amplitude of 3 mm) were added during each 1-minbout @WLT+20%D in order to reduce the decrease in VO2 during this lower exercise intensity.Vibrations induced a significant increase of absolute and relative VO2 and total time spent above 90% VO2max.This may at least partly be due to the increased muscle activation in lower and upper limbs observed during the 1-min bouts at WLT+20%D